Review: The Emerging Role of Metformin as Aromatase Inhibitor in Breast Cancer - Amrilmaen Badawi (UMI Medical Journal, 2019)
The prevalence of breast cancer is still very high among women, in particular post-menopausal women. There are many factors contributed to the diseases, including diabetes. Recently, it has been emerged that metformin, an antidiabetic agent, is capable of reducing the risk of developing breast cancer among post-menopausal women, and act as aromatase inhibitors (AIs) which inhibits the production of estrogen. In this review, we focus in discussing the possible work mechanism of metformin as AIs and what is in the pipeline on clinical trials.